An Investigation into the Green Marketing Effects on Green Consumerism - Tuz, Ahmet; Sertyeşilışık, Begüm (Journal of Applied And Theoretical Social Sciences, 2022)
Having become more attention grabbing lately, green marketing (GM) is a concept that affects consumers with respect to their purchasing decisions. The priority for consumers gradually concern environment-friendliness of products/services. Thus, market segmentations started to expand to include environmental concerns. A number of studies regarding GM can be found in the literature, as well as green purchase intention (GPI) and green purchasing behavior. The majority of the existing studies concern target market segmentation with respect to demographic variables within the same country and specifically concerning the evaluation of environmental purchasing behavior. However, there are limited studies in the literature, investigating green consumerism from an international point of view. This study analyses the relationship of international consumers’ green self-identification levels. In this study, international participants are at the postgraduate level. It is aimed to evaluate how the green self-identification of consumers with the same education level is related to their green product awareness (GPA) and GPI and price sensitivities (PS). A total of 119 respondents filled the questionnaire. Data was analyzed later with SPSS 23. Findings showed that respondents, who define themselves to be environment-friendly, tended to be more aware of green products, in addition to the tendency that GPA has a significant impact on GPI and GPA and that GPA has a significant impact on GPI. Furthermore, the study concluded that the tendency that country significantly affects environment-friendliness. This study is hoped to be useful for researchers and practitioners in the field, who wish to focus on international green consumerism.